The congruence effects of Confucian and western management values on individual and organizational performance: Evidence from the Korean public sector - Kim, Min Young (Animo Repository, 2021)
This study examines the effect on Korean public employees’ in-role performance and organizational performance of Confucian values and of two organizational management values developed in the West, specifically collective public service motivation-oriented (PSMO) management values and entrepreneurship-oriented (EO) management values. Using data from the Public Sector Entrepreneur- ship Survey the study finds that some Confucian values can enhance in-role and organizational performance in the Korean public sector, but others can have negative or no effects. The mixed results suggest that the relationship may be more complex than assumed and that some variables may mediate the effects. This has implications on how the positive effects of Confucian values on performance can be maximized while minimizing the negative effects. The collective PSMO and EO management values developed in the Western context both enhance in- role performance but only EO management values positive effects extend to organizational performance.Lastly, the study finds that the data does not sup- port the hypothesized positive interaction effects between Confucian values and PSMO and EO management values and both in-role and organizational performance. More investigation is required to fully understand these interaction effects.